Atuação do fonoaudiólogo nos núcleos de apoio à saúde da família na Paraíba : tecendo os fios entre a fonoaudiologia e a saúde coletiva - Costa, Lívia Sales da (2011)
The Core of Family Health Support represents today a scenario that reveals the actions of the speech therapist in the field of collective health. This study sought to examine the actions of the speech therapist in teams of Cores to Support Family Health, in municipalities from the State of Paraíba, in the perspective of health promotion. It is a qualitative research and its empirical material was constructed through semi-directed interviews in the period from april to june 2011, held with 12 speech therapists. The analysis was made according to the technique of discourse analysis with French trend. Three discursive formations were produced: 1) perceptions of the speech therapist about the core of support for family health and collective health; 2) the practice developed by the speech therapist in the core of support for family health and her understanding of health promotion; 3) the difficulties encountered for the development of professional practice at the core of support for family health. At the first discursive formation the audiologists presented difficulties in conceptualizing nucleus of support to family health and collective health, a fact that may result in a worker process distanced from the conception of health promotion. In the second formation, the subjects are positioned in order to inform you that, although the work of the core teams to support family health is aimed at health promotion, its practice is still centered on the individual care and curative, which reinforces its characteristic of rehabilitation. In the third formation, the discursive fragments show that the worker process of the speech therapist is impacted by difficulties in physical structure, transport and material resources and by the interaction between the teams of the family health strategy and the teams of the Core of Support for Family Health. They also reveal overhead activities and incomprehension of managers on the working of speech therapists. As part of collective health, discursive formations indicate that the practice of these professionals need to be reconsidered in view of the importance of ruptures that strengthen the model of health promotion, in order to extend the actions of these professionals beyond the individual care, curative and rehabilitative.